Discours sur l'éducation au XVIIIe siècle Pédagogie et utopies pédagogiques - Baggerman, Arianne (Etudes sur le XVIIIe siècle series, 2021)
John Locke's publication of his famous Essay Concerning Human Understanding (1690), followed by Some Toughts Concerning Education (1694), marked a real turning point in European discourse on education.